(untitled) (Bulletin KNOB, 2009)
A city is not built with the intention of becoming world heritage. This value is attributed to it on the basis of what it has produced in a spatial-physical sense in the course of time, as a reflection of its view of life and way of life, its administrative ambitions and social-economic needs. While the municipality of Amsterdam is awaiting a definite answer about placement of the seventeenth-century ring of canals on the World Heritage List, there are two cities across the Atlantic Ocean that preceded it in this respect and may serve as valuable examples for the actual execution. These are the historical city centres of Willemstad and Paramaribo, which were proclaimed world heritage in 1997 and 2002 respectively. Both in Willemstad and in Paramaribo it concerns an urban development process directed by the Netherlands for centuries on end; a colonial past that increases the complexities and stratification of the world heritage list. Preservation of heritage from the past may give shape to the local, contemporary urban culture, but has hardly played any part in it so far. The fact that they were placed on the World Heritage List appears to have been a last resort for both Willemstad and Paramaribo in order to be able to safeguard the special cultural values of their highly neglected historical city centres. Thus this situation reverts directly to the original goal of the World Heritage Convention of 1972, namely by means of international aid rescuing valuable cultural and natural heritage that is in danger of being lost. Although, notably these past years, both historical city centres are getting more international attention, it was not possible to prevent further decay and destruction of these historical city centres, even after having been placed on the World Heritage List. In the daily practice of both cities assuming responsibility for their world heritage proves difficult to put into operation. The current developments and struggles in Willemstad and Paramaribo show that the significance of world heritage for the local, daily practice has been small so far. This significance is mainly expressed in the increased possibilities of exploiting the local historical heritage as a tourist attraction. This may have to do with the fact that in both cities the (universal) cultural values of the historical city centres attributed from a historical point of view have not been translated into operational values for the local practice yet and are therefore intangible for owners, investors and designers. Dilemmas in management arise when only limited financial resources are available, maintenance and restoration programmes and incentive schemes are lacking, the structure of the executing organization is faltering, understaffed or not firmly rooted administratively, the local reality is guided by ad hoc initiatives and informal building practices, and when execution of and compliance with existing laws and regulations are seriously inadequate. A management plan by itself cannot change this. Discussions on when heritage is of universal value for mankind, on the qualitative diversity in composition of the World Heritage List and on when heritage is in danger or should be placed on the World Heritage in Danger List, are politically and scientifically interesting on a higher abstraction level and have frequently been held, but eventually they have not contributed in any essential way to the survival of heritage (in danger), which is the primary goal of the World Heritage Convention. After all, the survival of urban heritage is not determined internationally, but is eventually fought out and realized by all the parties involved in the daily, local practice, which cannot be included in a management plan. In practice a supplementary, process-based commitment to world heritage is of overriding importance. By paying attention to the special qualities of one’s own cultural history and its material and immaterial references, by making its values operational in planning processes and by positioning the historical city centre as an essential element of contemporary culture, world heritage will acquire new significance. The highly politicized and not easily accessible – because very much specialist- oriented – organization that the UNESCO is at the moment, ought to become less bureaucratic and might start to function more as a platform and interactive network for exchange of knowledge and development of knowledge on preservation and management methods for heritage.